Peran Hormon Pertumbuhan dalam Regulasi Metabolisme Energi, Pertumbuhan Linier, dan Implikasi Klinis pada Gangguan Endrokin - Akmal Alif Muzakki; FA Elang Pujangga; Muhammad Daffa Radithya; Liss Dyah Dewi Arini (STIKes Ibnu Sina Ajibarang, 2025)
Growth hormone (GH) is a peptide hormone secreted by the anterior pituitary gland, playing a vital role in regulating body growth and energy metabolism. This article explores the role of GH in supporting linear growth through the stimulation of insulin-like growth factor-1 (IGF-1), its influence on lipid, protein, and carbohydrate metabolism, and the clinical implications of GH production disorders, including dwarfism, gigantism, and acromegaly. The research method employed is a literature review from various recent scientific sources, including journals, textbooks, and research articles. The findings indicate that GH functions to enhance lipolysis, protein synthesis, and maintain blood glucose levels, making it a key hormone in metabolic regulation. Moreover, GH production abnormalities can lead to long-term health issues, such as obesity, insulin resistance, and other metabolic complications. A deeper understanding of GH mechanisms opens opportunities for the development of hormone-based therapies to manage these disorders.